2002
DOI: 10.1046/j.1471-6712.2002.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Need assessment and quality of life in outpatients with schizophrenia: a 5‐year follow‐up study

Abstract: The present study is a 5-year follow-up of patients with schizophrenia who were in-patients for more than 3 months in 1993. In all, 19 patients fulfilled the criteria and were interviewed 6 months after their discharge. Seventeen of them also participated in a follow-up 5 years later. Their needs were independently rated by themselves and by their key workers according to the Camberwell Assessment of Need (CAN, research version 3.0). The interview with the patients also included quality of life assessed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
16
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 21 publications
8
16
0
2
Order By: Relevance
“…Finally, there some differences between patients’ and relatives’ reports in individual domains of the CAN-R and the type of unmet needs, with relatives usually placing more emphasis on social and informational needs than the patients themselves. This was in line with most of the previous research on the subject, which has indicated that relatives generally report greater number of needs, and/or their perceptions regarding areas of need differ from those of patients[9,36,38,39]. Differing views of needs among patients and relatives could be a consequence of the additional component of caregiver-burden that relatives have to face, since certain studies have found that a higher level of caregiver-burden is usually associated with higher levels of expressed needs and differences in the types of needs reported by relatives[9,40].…”
Section: Discussionsupporting
confidence: 91%
“…Finally, there some differences between patients’ and relatives’ reports in individual domains of the CAN-R and the type of unmet needs, with relatives usually placing more emphasis on social and informational needs than the patients themselves. This was in line with most of the previous research on the subject, which has indicated that relatives generally report greater number of needs, and/or their perceptions regarding areas of need differ from those of patients[9,36,38,39]. Differing views of needs among patients and relatives could be a consequence of the additional component of caregiver-burden that relatives have to face, since certain studies have found that a higher level of caregiver-burden is usually associated with higher levels of expressed needs and differences in the types of needs reported by relatives[9,40].…”
Section: Discussionsupporting
confidence: 91%
“…More than one-third of the patients expressed a need concerning mental health, accommodation, and work / occupation. Furthermore, the intensity of the provided services was highest in these areas, which has been reported in earlier studies [10,33,39] .…”
Section: Discussionsupporting
confidence: 79%
“…Patients in psychiatric care want a more active role in treatment (38) and service planning (39). Foldemo and Brogren (40) found in a study that there was a difference between how the key staff and the outpatient with schizophrenia rated the needs. This confirmed how important it is that there should be patient and staff co‐operation in the planning of care .…”
Section: Discussionmentioning
confidence: 99%